Effect of a stroke support service in Germany: a randomized trial. Issue 6 (18th August 2015) - Saal, Susanne; Becker, Christiane; Lorenz, Silke; Schubert, Michael; Kuss, Oliver; Stang, Andreas; Müller, Tobias; Kraft, Andrea; Behrens, Johann
Abstract : Purpose: This trial investigated the effect of a stroke support service on physical functioning in post-stroke outpatients. Methods: The randomized trial took place in two urban hospitals in Germany. The intervention covered a post-discharge stroke support service including following components: outreach work (via telephone contact and home-visit), informational events, training sessions, online portal, and written patient information. The control group received optimized standard care by written patient information. The primary outcome measure was physical function assessed by the physical scale of the stroke impact scale (SIS) 2.0 at baseline and after 12 months follow-up. Secondary outcomes covered health-related quality of life, depression, somatization, reinfarcts, and mortality. Use of health services was recorded. Results: A total of 265 patients were randomized either to the intervention ( n = 130) or to the control group ( n = 135); n = 230 patients were analyzed after 12 months. The mean group difference on the physical SIS scale was − 2.7 points (95% CI, − 5.5–0.2) in favor of the control group. The overall risk of mortality in the control versus the intervention group was 11.6and 3.9%, respectively (hazard ratio 0.32, 95% CI, 0.12–0.88). All other outcomes were neither statistically nor clinically relevant, different between the two study groups. Conclusion: An additional stroke support service did not improve physical function, health-related quality of life, depression, somatization, or reinfarcts in stroke patients. Data suggest a lower overall risk of mortality in the intervention group.